APPLICATION OF POINT OF SALES WEB STORE DVD / VCD USING PHP CONTENT MANAGEMENT SYSTEM (JOOMLA) - Cherry Mariz Wibowo; Ire Puspa Wardhani, Ir, MMSi (Jurnal Sistem Informasi, 2008)
Content Management System (Conten Management System) known as the CMS is aweb-based application that has such a system to provide convenience to the users aswell as its organizer.In accordance with CMS's own name, a website that implements this system isoriented towards content. It was not a significant constraint to management or publicrelations a company, institution, or organization to update its website. With accessrights and authority of each, every part of the company, institution, or organizationcan contribute to this website without difficult procedures.